Evaluation of secretory activity in carp pancreatocytes (Cyprinus carpio L.) when using lactobacillus-based chelate and probiotic supplemental feed complexes - D. Nikiforov-Nikishin; S. Antipov; N. Kochetkov; A. Nikiforov-Nikishin; T. Bychkova (Brazilian Journal of Biology, 2021)
Abstract The experimental research was carried out on the juvenile carp (Cyprinus carpio L.). The impact from supplemental feeds consisting of variable concentrations of chelate compounds, biogenic trace elements and probiotic lactobacillus-based product Bacillus subtilis VKPM B-2335 was evaluated. Optical and qualitative parameters of the lactobacillus base were studied in order to identify the major group of substances potentially able to influence the end result. The purpose of this research was to identify changes in the structure of the zymogen granules and their dimensions at which supplemental feeds produce a stimulating effect on the synthesis of zymogens in exogenous cells of the secretory part of pancreas. At the outcome of the study, for the first time, it was possible to prove that the integrated action of chelates and lactobacillus-based probiotics complemented each other. Metal chelate compounds contributed to enlargement of the zymogen granules, if compared to the control values. The bacterial products accelerated production of the zymogen granules in acinar cells diffusely located in carp hepatopancreas.